KARAKTERISTIK KAPAL KARAM DI LAUT JAWA UTARA CIREBON - Kelana Asmarajaya, I Putu (Humanis, 2015)
This study is concerned with the characteristic of shipwrecked in Java sea northern part of Cirebon, particularly about the identification and the finding of the ship therefore the origin could be traced. The characteristic of the ship being analyzed among others are : the flank, keel, and the technique of the ship making. The analysis of the findings concerns with ceramics and some metal stuffs. This study is aimed to be a reference for another related study or be an additional knowledge.
Keywords: characteristic of shipwreck